Visual Narratives in Health Communication: Evaluating Comics as Tools for Health Literacy by the Indonesian Ministry of Health - Sabri, Sabri; Adiprabowo, Vani Dias; Sumarlan, Iman; Mohamad, Rafidei (Universitas Ahmad Dahlan, 2024)
This study investigates the efficacy of comics as a strategic communication tool for health promotion, utilizing a qualitative analysis of literature and examples from the “Sehat Negeriku” website managed by the Indonesian Ministry of Health. The multifaceted nature of comics, incorporating visual storytelling and character-driven narratives, offers a unique method for conveying complex health messages in an accessible and engaging manner. This research identifies several key advantages of comics in health communication, including increased appeal and interest among diverse demographics, enhanced memory retention through visual cues, emotional engagement that deepens message impact, stimulated creativity and imagination, and the ability to reach a broad audience. Data collection involved a thorough review of existing literature and content analysis of health communication comics, focusing on their structure, content, and reception. The findings highlight how comics, by blending entertainment with educational content, can effectively reduce resistance to health messages, facilitate behavioral change, and contribute to public health knowledge. Furthermore, the study underscores the importance of considering cultural relevance and audience-specific characteristics in comic design to maximize their educational impact. This paper contributes to the understanding of visual communication in public health and supports the integration of comics into broader health promotion strategies.